RESENSI BUKU NONFIKSI: BUKU PENGANTAR SEMANTIK BAHASA INDONESIA KARYA ABDUL CHAER - Hasibuan, Syahputri Mariani; Gustianingsih; Cindy Roulina Siallagan; Sheilla Josana; Hillya Mahzarina; Winny Stefanie (Indonesian language and literature education program Majapahit Islamic University, 2024)
Review is an activity of evaluating works that have been read, watched or listened to, whether in the form of books, films, articles or other works. In this research, the work that will be reviewed by the author is a nonfiction book entitled Introduction to Indonesian Semantics by Abdul Chaer. This research aims to provide a comprehensive overview and critical assessment of the content and structure of the book. Through a qualitative approach, this research analyzes the text of the book in depth so that it can show the advantages, disadvantages and contribution of the book to the study of Indonesian semantics. It is hoped that the results of this research can contribute to the development of Indonesian semantic studies, especially for students, researchers and general readers who are interested in semantic studies. Keywords : Review, nonfiction, qualitative